2018
DOI: 10.1007/s11060-018-2789-5
|View full text |Cite
|
Sign up to set email alerts
|

Renin angiotensin system and its role in biomarkers and treatment in gliomas

Abstract: Gliomas are the most common primary intrinsic tumor in the brain and are classified as low- or high-grade according to the World Health Organization (WHO). Patients with high-grade gliomas (HGG) who undergo surgical resection with adjuvant therapy have a mean overall survival of 15 months and 100% recurrence. The renin-angiotensin system (RAS), the primary regulator of cardiovascular circulation, exhibits local action and works as a paracrine system. In the context of this local regulation, the expression of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 130 publications
1
26
0
Order By: Relevance
“…The current understanding of RAS is far more complex than its classic point, and two significant concepts have been added. First, the system is not only expressed at a systemic level but also works locally in a paracrine function in the vasculature, kidney, heart, lungs and CNS et al [16]. In our study, we found that serum concentrations of Ang II and NA were elevated in HFMD cases, especially in severe cases, suggesting RAS activation.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The current understanding of RAS is far more complex than its classic point, and two significant concepts have been added. First, the system is not only expressed at a systemic level but also works locally in a paracrine function in the vasculature, kidney, heart, lungs and CNS et al [16]. In our study, we found that serum concentrations of Ang II and NA were elevated in HFMD cases, especially in severe cases, suggesting RAS activation.…”
Section: Discussionsupporting
confidence: 52%
“…Peripheral vasoconstriction will cause vascular endothelium injury and increased permeability, further inducing blood accumulation in the lower pulmonary region [12][13][14][15]. The RAS plays a critical action regulating the circulation in the human body in response to low blood pressure or decrease in serum sodium levels [16].A component of this system is angiotensinogen (AGT) that is synthesized and released by the liver into the general circulation. AGT is converted through another reaction into angiotensin I (Ang I) by the protein renin from the renal juxtaglomerular apparatus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of GBM EC-enriched genes we identified are linked through the renin-angiotensin system (RAS): angiotensin I converting enzyme (ACE), glutamyl aminopeptidase (ENPEP) and NADPH oxidase 4 (NOX4). RAS inhibitors suppress progression and lengthen survival period in several cancer types (Ishikane and Takahashi-Yanaga, 2018; Pinter and Jain, 2017), including glioma (Levin et al, 2017), where they have a broad spectrum effectiveness, and are currently being considered for inclusion in treatment protocols (Perdomo-Pantoja et al, 2018). ACE and ENPEP are central enzymes in the RAS, catalysing the conversion of angiotensin I to angiotensin II, and angiotensin II to angiotensin III, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ACE and ENPEP are central enzymes in the RAS, catalysing the conversion of angiotensin I to angiotensin II, and angiotensin II to angiotensin III, respectively. Angiotensin II and III have various effects, mediated primarily through angiotensin receptor I (ATR1) (Jackson et al, 2018), such as the induction of pro-survival signalling, via NF-KB mediated anti-apoptotic molecules, or through PI3K-Akt mediated suppression of caspases (George et al, 2010), the induction of cellular proliferation (Clark et al, 2011; Perdomo-Pantoja et al, 2018) and loss of blood brain EC barrier properties (Biancardi and Stern, 2016). More high grade astrocytoma tumour cells express ATR1, compared to lower grade, and expression is associated with cell proliferation, vascularisation and shorter survival (Arrieta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%